2012
DOI: 10.3390/jfb3030544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medium and Temperature on Cellular Responses in the Superficial Zone of Hypo-Osmotically Challenged Articular Cartilage

Abstract: Osmotic loading of articular cartilage has been used to study cell-tissue interactions and mechanisms in chondrocyte volume regulation in situ. Since cell volume changes are likely to affect cell’s mechanotransduction, it is important to understand how environmental factors, such as composition of the immersion medium and temperature affect cell volume changes in situ in osmotically challenged articular cartilage. In this study, chondrocytes were imaged in situ with a confocal laser scanning microscope (CLSM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In previous studies the speed of RVD in isolated chondrocytes reduces at temperatures below 37 C 11,12,15,42 . However, a recent study by Huttu et al showed temperature doesn't affect chondrocyte volume regulation in situ 43 . In our study, conducted at room temperature, 65.6% of chondrocytes exhibited RVD in response to sudden hypoosmotic challenge.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies the speed of RVD in isolated chondrocytes reduces at temperatures below 37 C 11,12,15,42 . However, a recent study by Huttu et al showed temperature doesn't affect chondrocyte volume regulation in situ 43 . In our study, conducted at room temperature, 65.6% of chondrocytes exhibited RVD in response to sudden hypoosmotic challenge.…”
Section: Discussionmentioning
confidence: 96%
“…We believe that this is acceptable because the weight fraction of the nanoparticles in the dry microparticles is very low (∼0.67%). The molarity of DMEM has been reported as 0.29 M . We assume that the complete medium, which was DMEM supplemented with 10% FBS and antibiotics and l -glutamine, had the same molarity, that is, M medium = 0.29 M. Kawasaki et al found that the partition coefficient, K , for Na + and Cl – ions and collapsed PNIPAM gel is ∼0.15 in 0.3 M NaCl at 40 °C .…”
Section: Resultsmentioning
confidence: 99%